PENGARUH KEPEMILIKAN ASING, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN SEKTOR KESEHATAN: in; - Angga Angga; Nesti Hapsari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The health sector is one of the strategic sectors in a country's economy The Covid-19 pandemic has made many very significant changes in various company sectors. The healthcare sector is one of the most affected. In the face of this problem, foreign, institutional, and managerial ownership affect the company's strategy and its decisions, which in turn can have an impact on its value. This study uses a quantitative research design. The data source used by researchers in this study is secondary data. This data comes from the financial statements of health sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. In secondary data, data collection is more likely to be carried out through a documentation system and literature review. Data analysis uses the Classical Assumption Test, Descriptive Statistical Analysis, Multiple Linear Regression Analysis, Determination Coefficient Test and Hypothesis Testing. Foreign Ownership has no effect on Firm Value, Institutional Ownership affects Firm Value, Managerial Ownership has no effect on Firm Value, and Foreign Ownership, Institutional Ownership, and Managerial Ownership simultaneously together affect Firm Value.